Barriers to trade in environmental goods: How Important they are and what should developing countries expect from their removal - Jaime de Melo; Jean-Marc Solleder (Fondation pour les études et recherches sur le développement international (FERDI), 2018)
Few developing countries have participated in the environmental goods agreement (EGA) negotiations to reduce barriers on trade in Environmental Goods (EGs). Reasons for this reluctance are first reviewed along with a comprehensive description of barriers to trade (tariffs and NTBs) on two lists of EGs used in negotiations comprised mostly industrial products (The APEC and WTO lists), and a third, a list of Environmentally Preferable Products (EPPs) more representative of the perceived interests of developing countries. The paper then revisits and extends the literature on the estimation of barriers to trade in EGs for these lists. These estimates are carried out with a structural gravity model and new data: (i) on bilateral (rather than MFN) tariffs, and; (ii) with a measure of regulatory overlap in bilateral trade to capture the often-observed pattern of greater bilateral trade among countries that share similar regulatory regimes. Results show that tariffs generally reduce the intensity of bilateral trade, often with little difference in statistical significance between the EG and non-EG group for each list. Regulatory harmonization, as captured by an increase in regulatory overlap is also estimated to be conducive to more intense bilateral trade.
Keywords: F18; Q56; 330